Volcano flank terraces on Mars - Byrne, Paul K. (Trinity College (Dublin, Ireland). Department of Geology, 2010)
Flank terraces are topographically subtle, laterally extensive structures on the flanks of several large shield volcanoes on Mars. The formation of terraces has been ascribed to several mechanisms, including elastic self-loading, lithospheric flexure, gravitational spreading, magma chamber tumescence, and shallow slumping. The geometry of these structures, in terms of morphology and distribution, is poorly understood. In turn, proposed formation mechanisms have not been investigated fully. Therefore, flank terraces have yet to be integrated into the current framework of Martian volcanotectonism.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin